Norwegian prospective teachers’ MKT when interpreting pupils’ productions on a fraction task - Jakobsen, Arne; Ribeiro, C. Miguel; Mellone, Maria (NOMAD Nordic Studies in Mathematics Education, 2014)
This paper focuses on Norwegian prospective primary teachers’ mathematical knowledge for teaching (MKT) when interpreting and making sense of pupils’ answers. We named such knowledge interpretative knowledge and we consider it to be linked with common content knowledge and specialized content knowledge. In order to deepen these links and to access and develop such knowledge in prospective teachers, we designed a suitable set of tasks on a problem concerning fractions in order to investigate this particular kind of knowledge and clarify its features and dimensions. The results reveal the importance of developing such types of knowledge as a basis for teachers to effectively make sense and interpret pupils’ productions and to make it possible to provide effective and meaningful feedback.